Occurrence and removal of estrogens, progesterone and testosterone in three constructed wetlands treating municipal sewage in the Czech Republic - Vymazal, Jan; Březinová, Tereza; Koželuh, Milan (The Science of the total environment, 2015)
Estrogenic hormones, progesterone and testosterone are endocrine-disrupting chemicals and their presence in aquatic environments represents a potentially adverse environmental and public health impact. There is a considerable amount of information about removal of estrogens, progesterone and testosterone in conventional wastewater treatment plants, namely activated sludge systems. However, the information about removal of these compounds in constructed wetlands is very limited. Three constructed wetlands with horizontal subsurface flow in the Czech Republic have been selected to evaluate removal of estrogens (estrone, estriol, 17β-estradiol, 17α-ethinylestradiol), testosterone and progesterone. Monitored constructed wetlands for 100, 150 and 200 PE have been in operation for more than 10 years and all systems exhibit very high treatment efficiency for organics and suspended solids. The results indicate that removal of all estrogens, progesterone and testosterone was high and only estrone was found in the outflow from one constructed wetland in concentrations above the limit of quantification 1 ng l(-1). The limits of quantification for other estrogens, i.e., 10 ng l(-1) for estriol, 1 ng l(-1) for 17β-estradiol and 2 ng l(-1) for 17α-ethinylestradiol were not exceeded in the outflow of all monitored constructed wetlands. Also, for progesterone and testosterone, all outflow concentrations were below the LOQ of 0.5 ng l(-1). The results indicated that constructed wetlands with horizontal subsurface flow are a promising technology for elimination of estrogens, progesterone and testosterone from municipal sewage but more information is needed to confirm this finding.
Keywords: mokřady; Waste Water; estrogeny; Constructed wetlands; odpadní voda; Česká republika; Hormones; Sewage; Testosterone; endokrinní disruptory; Czech Republic; chemické látky znečišťující vodu; testosteron; Waste Disposal, Fluid; odpad tekutý - odstraňování; Wetlands; progesteron; Water Pollutants, Chemical; Endocrine Disruptors; Wastewater; Estrogens; Biodegradation; Progesterone